ESG AND FIRM PERFORMANCE: THE MODERATING ROLE OF BOARD DIVERSITY - Amalia Adnindya; Mitha Dwi Restuti (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
ESG likely affects firm performance because better ESG practices improve firm image among investors, stakeholders, and the public. Besides, ESG practices will reduce long-term operating costs and facilitate firms to acquire access to capital from their investors. In this respect, board diversity, especially gender and age, is critical because boards of directors are crucial in implementing ESG practices. Board diversity likely strengthens or weakens the relationship between ESG performance and firm performance. This study seeks to test the impact of ESG on firm performance among Indonesian publicly listed firms in 2014-2022. Studies on ESG in Indonesia, especially using ESG scores, remain limited, thus necessitating further studies. Our sample is Indonesian firms engaging in ESG practices, as indicated by ESG score in 2014-2022, resulting in 305 firm-year observations. We test the hypotheses using multiple linear regression. The results demonstrate that ESG positively affects firm performance. Further, board diversity, especially gender, strengthens the positive impacts of ESG performance on firm performance. Nevertheless, the board of directors’ age diversity does not moderate the positive effect of ESG on firm performance, suggesting that better ESG practices will improve firm performance and the impact is stronger when firms have more female directors.